Motor Deficits in an Alpha-Synuclein Mouse Model of Parkinson's Disease are not Exacerbated by Gba1 Mutation - Fitzpatrick, Megan E. (Université d'Ottawa / University of Ottawa, 2017)
Parkinson’s disease is a movement disorder characterized by nigrostriatal dopamine pathway degeneration and neuronal α-synuclein accumulation. Pathogenesis is associated with mutations in α-synuclein and Gba1 encoding alleles. Animal models created to date do not recapitulate the spectrum of clinical disease features. This thesis characterizes the bi-genic Synergy mouse, hypothesized to demonstrate motor behavioural and histological abnormalities downstream of α-synuclein overexpression and mutated Gba1. Synergy and SNCA mice (overexpressed α-synuclein with wild-type Gba1) have early onset deficits in motor coordination, muscle strength and nest building. Both exhibit increased α-synuclein concentration in the brain and cerebellar inclusions positive for two markers of pathological α-synuclein processing. Overall mutant Gba1 expression within Synergy mice does not worsen the behaviour or the histopathological findings associated with overexpression of human α-synuclein in SNCA mice. Future studies will determine whether mutant Gba1 expression alters cognitive behaviour and/or lipid homeostasis in this new bi-genic model of Parkinson’s disease.
Keywords: Parkinson's disease; mouse model; Gba1; alpha-synuclein; motor behaviour; brain pathology